ANALISIS RASIONALISME DALAM PERSPEKTIF SILA KEADILAN SOSIAL DAN IMPLEMENTASINYA DALAM PENYALURAN BANTUAN LANGSUNG TUNAI DI KELURAHAN BULAKREJO - Wardhana, Wisnu; Patmisari, Patmisari (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2024)
This study aimed to find out the mechanism of Direct Cash Assistance (BLT), the challenges and solutions faced, and the implementation of the social justice principle in the Direct Cash Assistance (BLT) in Bulakrejo Village, Sukoharjo Regency. A qualitative descriptive method was used to collect data through observation, interviews and documentation. The series of research activities were divided into three stages, namely research planning, research implementation, and research report. The results of this study showed that the mechanism of data collection for prospective Direct Cash Assistance (BLT) was carried out by the Sukoharjo Regency Social Service using the Integrated Social Welfare Data (DTKS) while the distribution mechanism was carried out at the post office by postal officers or at the Bulakrejo Village by the Kaur/Kasi. The obstacles in the distribution of Direct Cash Assistance (BLT) in Bulakrejo Village included the Direct Cash Assistance (BLT) acceptance was not on target, there were data errors in the form of National Identity Number (NIK), and difficulties in meeting prospective Direct Cash Assistance (BLT) recipients. The implementation of the Direct Cash Assistance (BLT) program in Bulakrejo Village requires follow-up efforts to realize the principle of Social Justice for All Indonesian People